Estudio de prefactibilidad para la instalación de una planta de producción de muebles RTA (Ready to assemble) enfocado a retailers como punto de venta - Mondragón Graham, Héctor Rodolfo (2016)
This project was carried out in order to determine the feasibility of installing a RTA (Ready to Assemble) furniture plant. In the beginning of it, technical, economic and social justifications were made, which showed evidence of the economic growth of Peru, the large amount of ready workforce and the opportunity to support the social growth of the area.